Organizational assessment and improvement in the public sector workbook - Immordino, Kathleen M. (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
"Grounded in organizational theory, this book addresses the practical aspects of assessment implementation, providing practical methodology for implementation. It can be used not only to implement the Public Sector Assessment and Improvement (PSAI) model, but its pre-assessment readiness perspective means that it can be used with any assessment model from PSAI and Baldrige to a more basic SWOT analysis or organizational survey. It supplies strategies to address the real fiscal limitations of practitioners and at the same time to get the tools needed for assessment into the hands of those who can best use them"--
Includes bibliographical references (pages 171-180) and index.
Keywords: Organizational effectiveness -- United States -- Evaluation; Administrative agencies -- United States -- Management -- Evaluation; BUSINESS & ECONOMICS / Quality Control; POLITICAL SCIENCE / Public Affairs & Administration